Resignificación del rol materno: Narrativas de madres estudiantes universitarias. - Guayanay Calva, Jessenia Marilú (2018)
The objective of this research is to identify which meanings university students assign to their maternal role in the context of the Universidad Técnica de Cotopaxi. For this purpose, the project focused on identifying the narratives of students who are mothers, for that reason the qualitative methodology was used through the Historias de Vida method with the in-depth interview technique. The sample consisted of mothers-students of the Faculty of Ciencias Humanas y Educacion, through the application of instruments focused on the subcategories: maternal role, family, university and economy. Among the main results, the role played by the family of the students is highlighted. Thus, they can carry out this double role of mothers- tudents; In addition, the type of relationship that the students maintain with the rest of the members of their family was identified. It is expected that this research project might contribute to the identification of the role that the university should fulfill in relation to the situation of students who must fulfill that double role.